2020
DOI: 10.3168/jds.2019-17155
|View full text |Cite
|
Sign up to set email alerts
|

Hay or silage? How the forage preservation method changes the volatile compounds and sensory properties of Caciocavallo cheese

Abstract: The aim of this study was to determine the effect of the forage preservation method (silage vs. hay) on volatile compounds and sensory properties of a traditional Caciocavallo cheese during ripening. A brown-midrib sudangrass hybrid was cultivated on a 7-ha field and at harvesting it was half ensiled in plastic silo bags and half dried to hay. Forty-four lactating cows were equally allotted into 2 groups fed a isonitrogenous and isoenergetic total mixed ration containing as the sole forage either sorghum hay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…We observed no differences in the intensity of flavor descriptors of the cheeses between herbage conservation methods, which substantiates previous findings by Verdier-Metz et al (1998) on Saint-Nectaire cheeses derived from cows fed hay and silage from the same plot of native mountain grassland. In contrast, studies of Verdier-Metz et al (2005) and Serrapica et al (2020) reported some flavor differences related to the herbage conservation method. Such sensory differences may be due to a different dietary proportion of dicotyledonous species (ryegrass silage from temporary grassland versus permanent grassland hay; Verdier-Metz et al, 2005), or they could be related to the specific forage types (i.e., sorghum) and the specific processing technology of stretched curd cheeses (Serrapica et al, 2020).…”
Section: Differences Between Milk and Cheese From Cows Fed Hay Or Silagementioning
confidence: 89%
See 1 more Smart Citation
“…We observed no differences in the intensity of flavor descriptors of the cheeses between herbage conservation methods, which substantiates previous findings by Verdier-Metz et al (1998) on Saint-Nectaire cheeses derived from cows fed hay and silage from the same plot of native mountain grassland. In contrast, studies of Verdier-Metz et al (2005) and Serrapica et al (2020) reported some flavor differences related to the herbage conservation method. Such sensory differences may be due to a different dietary proportion of dicotyledonous species (ryegrass silage from temporary grassland versus permanent grassland hay; Verdier-Metz et al, 2005), or they could be related to the specific forage types (i.e., sorghum) and the specific processing technology of stretched curd cheeses (Serrapica et al, 2020).…”
Section: Differences Between Milk and Cheese From Cows Fed Hay Or Silagementioning
confidence: 89%
“…However, the effect of herbage conservation per se on the sensory properties of milk and cheese in previous investigations was often confounded with the effect of botanical composition and phenological stage (i.e., the typically later harvest date for haymaking). To the best of our knowledge, only 2 experiments investigated the effect of forage conservation method using herbage harvested simultaneously from the same plot on cheese sensory quality and VOC profile: Saint-Nectaire type cheese from a permanent grassland (Verdier-Metz et al, 1998) and Caciocavallo, a stretched curd cheese, from a temporary subtropical grass (Serrapica et al, 2020). As the diet effects on the sensory properties differ depending on the cheese model (Verdier-Metz et al, 2005), validation by other cheese models is needed and the direct link of compositional changes to the sensory properties of milk and uncooked pressed cheese and their VOC profile has to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Values < 0.1 were not quantified. Further details are given elsewhere [33,34]. Milk clotting ability, expressed as rennet clotting time (r), curd-firming time (K 20 ) and curd firmness (A 30 ), was evaluated using a thromboelastograph (Formagraph, Foss Electric, Hillerød, Denmark) at the technical time of 30 min by adding to 10 mL of milk, at 35 • C, 0.2 mL of a diluted solution (1.6:100) of liquid rennet (1:15,000 rennet unit; 90% chymosin; Chr.…”
Section: Milk Yield and Qualitymentioning
confidence: 99%
“…Thus, they can significantly contribute to define cheese "terroir" and healthiness [5]. Several studies have focused on the effect of botanical diversity and preservation methods of forage (fresh, hay, or ensiled) on the quality of various cheeses [6][7][8][9]. In particular, it has been well established that pasture and fresh herbage can positively change the fatty acid (FA) composition of milk fat in terms of polyunsaturated fatty acids (PUFA).…”
Section: Introductionmentioning
confidence: 99%